Brigatinib combined with anti-EGFR antibody overcomes osimertinib resistance in EGFR-mutated non-small-cell lung cancer - Ken Uchibori (Nature Portfolio, 2017)
Resistance to EGFR-tyrosine kinase inhibitors in non-small-cell lung cancer is mediated by the C797S/T790M/activating mutation. Here, the authors identify brigatinib as a potential drug that in combination with anti-EGFR can overcome resistance in mutated cells.